DIVERSIFIKASI MIE SEHAT DENGAN BERBAHAN BAKUTEPUNG TERIGU DAN CAMPURAN TEPUNG BEKATUL - Ali Hasbi Ramadani, (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
Noodles made from wheat flour and rice bran are healthy foodsthat can be developed as a form of new business in the field of culinary, so as to strengthen the economic resilience of the community. The purpose of this researchwas to determine the physical characteristics of healthy noodles made from raw wheat flour and rice bran flour mixture,as well as taste trials on customer satisfaction. The research method used in this study using the experimental method which is thentested to 40 respondents. The results show that the most feasible in the production is 95% flour mixture and 5% Bekatul flour get the result of soft and soft dough as well as ordinary noodles, when inserted into the roll machine and noodle printers are good results and can be produced well, and when cooked and in add complementary almost no different from the noodle without rice bran, so it is feasible for the mass production. From the aspect kepusan customers generate 82.5% very satisfied, 17.5% Satisfied, 0% less satisfied, 0% not satisfied.